2017
DOI: 10.1111/jdv.14291
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose pulsed corticosteroid therapy combined with methotrexate for severe alopecia areata of childhood

Abstract: High-dose pulsed corticosteroid therapy combined with methotrexate for severe alopecia areata of childhood EditorAlopecia areata (AA) in childhood can run a chronic course and worsen over time. 1 Spontaneous hair regrowth is rarely appreciated in chronic severe AA. [2][3][4] Our centre described the ineffective use of high-dose pulsed corticosteroid therapy (HDPCT) in the long term. 1 Methotrexate (MTX) as a maintenance therapy following HDPCT showed some success in adults. 5 Although the evidence for using ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…Previous studies described the efficacy of MTX, alone or in combination with corticosteroids, for the treatment of extensive forms of AA with successful response in both adult and paediatric populations. [4][5][6] Other studies tested AZA alone 7,8 in the treatment of AA, with clinical outcomes and follow-up almost comparable to our experience. The association AZA plus MTX has never been experienced before in the treatment of severe forms of AA; however, the therapeutic concept has already been described by our group in adult patients with severe atopic dermatitis.…”
Section: Editorsupporting
confidence: 70%
See 2 more Smart Citations
“…Previous studies described the efficacy of MTX, alone or in combination with corticosteroids, for the treatment of extensive forms of AA with successful response in both adult and paediatric populations. [4][5][6] Other studies tested AZA alone 7,8 in the treatment of AA, with clinical outcomes and follow-up almost comparable to our experience. The association AZA plus MTX has never been experienced before in the treatment of severe forms of AA; however, the therapeutic concept has already been described by our group in adult patients with severe atopic dermatitis.…”
Section: Editorsupporting
confidence: 70%
“…Demographic and clinical characteristics at baseline, at 6 months and at 1 year are shown in Table 1. The simplified global score (SGS) 5 was assessed at 6 months and at Letters to the Editor 1 year of treatment, corresponding to 0 = no change, 1 ≤ 50%, 2 ≥ 50% to 99% and 3 = 100% hair regrowth. After 6 months of treatment, hair regrowth was recorded in 10 patients (55.5%), with SGS = 1 in eight patients and SGS = 2 in two patients.…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta‐analysis demonstrated reasonable effectiveness for MTX in patients with severe AA, with subgroup analysis demonstrating no difference in adverse effects in adults versus paediatric cases. However, there have only been a small number of studies reporting outcomes for MTX in childhood AA . In addition, these studies were all performed in American or European patient cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Many are brief, with scant or absent methodology and lack of follow‐up data. No studies mention blinding of outcome assessment and only one study utilized two separate assessors . The risk of publication bias is likely to be significant in such case series.…”
Section: Commentmentioning
confidence: 99%